1992
DOI: 10.1002/jnr.490310308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein kinase inhibitors on regeneration in vitro of adult frog sciatic sensory axons

Abstract: The effects of protein kinase inhibitors on regeneration in vitro of adult frog sciatic sensory axons were tested. Regeneration of crush-injured nerves for 8 days in serum-free medium was inhibited by staurosporine (100 nM) and H-7 (100 microM), which are both known to inhibit protein kinase C. With the use of a compartmented culture system it could be shown that H-7 exerted both local (outgrowth region) and central (ganglia) effects, the latter being more pronounced. The local effects could be due to reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…Furthermore, PKC␣ and -␤II were detected in the postsynaptic and the Schwann cells. These results are in accordance with those of other studies that have also suggested immunoreactivity for PKC␣ and -␤II in the Schwann cells of sciatic nerves (Ekström et al, 1992;Roberts and McLean, 1997). It has been reported that PKC␥ is restricted mainly to the CNS and spinal cord (Nishizuka, 1995), and we found that it is almost absent from the NMJ and extrasynaptic muscle.…”
Section: Immunohistochemical Cpkc Localization In the Nmjsupporting
confidence: 96%
“…Furthermore, PKC␣ and -␤II were detected in the postsynaptic and the Schwann cells. These results are in accordance with those of other studies that have also suggested immunoreactivity for PKC␣ and -␤II in the Schwann cells of sciatic nerves (Ekström et al, 1992;Roberts and McLean, 1997). It has been reported that PKC␥ is restricted mainly to the CNS and spinal cord (Nishizuka, 1995), and we found that it is almost absent from the NMJ and extrasynaptic muscle.…”
Section: Immunohistochemical Cpkc Localization In the Nmjsupporting
confidence: 96%
“…Cyclic AMP may play an important role in these processes (Cassel et al, 1982;Meador-Woodruff et al, 1984;Raff et al, 1978a,b;Salzer and Bunge, 1980). Following nerve injury, the in vivo proliferation of adult Schwann cells is accompanied by cAMP accumulation at the injury site (Carlsen, 1982;Ekstrom et al, 1992). In isolated Schwann cell cultures maintained in serum-free defined medium, growth factors including platelet-derived growth factor (PDGF), basic fibroblast growth factor (bFGF), transforming growth factor-b (TGFb), and insulinlike growth factor 1 (IGF-1) stimulate Schwann cell growth when presented to cells in combination with agents that increase cAMP (Chen et al, 1991;Davis and Stroobant, 1990;Eccleston et al, 1990;Schumacher et al, 1993;Stewart et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, PKC can phosphorylate STAT3 at Ser727, which is phosphorylated primarily by JAK at Tyr705 [32] . In the contrast, inhibition of PKC has been found to decrease the axonal growth [3,5,6,11,34,35] . These findings indicate that PKC participates in nerve regeneration after nerve injury.…”
Section: Discussionmentioning
confidence: 94%
“…This rapid increase in axonal PKC expression occurs within hours after nerve injury and has been shown to co-stimulate axonal regeneration with other factors [23] . In contrast, inhibition of PKC has been found to inhibit the regenerative axonal growth [3,5,6,11,34,35] . Also, PKC enzymes are important signaling molecules in preventing neurodegeneration after the nervous system injury.…”
Section: Introductionmentioning
confidence: 90%